Aplicación de textos narrativos para mejorar la comprensión lectora en estudiantes del cuarto grado del nivel primaria - Vasquez Narro, Max Erman (2022)
The objective of this Professional Assessment work is to improve reading comprehension _x000D_ levels through the proposal called Application of narrative texts to improve reading _x000D_ comprehension in fourth grade students of the primary level. With respect to the theoretical _x000D_ support of the present work, two variables were investigated; the first relates to narrative _x000D_ texts based on Chomsky's Constructivist theory and the reading strategies proposed by Solé _x000D_ (2002); the second variable is supported by the Schraw and Bruning theory (1996) who _x000D_ propose three epistemic models about reading: transmission, translation and transactional. _x000D_ On the other hand, in relation to the pedagogical support, the proposal of the Ministry of _x000D_ Education has been considered with respect to competence, capacity, standard, performance _x000D_ and the competency-based approach, the communicative approach of the Communication _x000D_ Area, the pedagogical and didactic processes for the competence and the type of evaluation _x000D_ applied in the learning session is the formative evaluation. Finally, it was concluded that _x000D_ there is a significant improvement in reading comprehension through narrative texts, _x000D_ showing in students the improvement through the answers to questions of the three levels of _x000D_ reading comprehension, deducing the meaning of some words according to the reading _x000D_ context.